Pathways from self-disclosure to medical coping strategy among adolescents with moderate and major depression during the COVID-19 pandemic: A mediation of self-efficacy - Yan Wu; Jing Shao; Dawei Zhang; Yongna Wang; Shufen Wang; Zhiren Wang; Yanhua Qu; Jianing Gu (Frontiers in Psychiatry, 2022)
BackgroundThe prevalence of adolescent depression in China during the COVID-19 pandemic is increasing. Self-disclosing depressive emotions could help release stress. Self-disclosure, which is a prerequisite for self-efficacy, can directly contribute to people’s psychological health, and depression and the choice of coping strategy are determined by the level of self-efficacy perceived.PurposeWe aimed to discuss the relationship between self-efficacy, self-disclosure, and medical coping strategy. Further, we explore the mediation effect of self-efficacy on the influence of self-disclosure on medical coping strategies in adolescents with depression.MethodsA total of 585 patients aged 11–24 years with moderate and major depression were recruited. All the assessments were completed on the second day after admission, including the General Self-Efficacy Scale (GSE), Distress Disclosure Index (DDI), and Medical Coping Modes Questionnaire (MCMQ). Pearson correlation was performed to explore the relationships of these variables. The bootstrap analysis was used to conduct to assess the mediation effects.ResultsBoth direct and indirect effects of self-disclosure on medical coping strategy were found. As predicted, self-efficacy partially mediated the relationship between self-disclosure and medical coping strategy (b = 0.0385, 95% CI: 0.0244–0.0538 for Confrontation; b = –0.0466, 95%CI: –0.0651 to –0.0296 for Resignation), respectively. The effect size for Confrontation and Resignation was 0.2659 and 0.2485, respectively.ConclusionSelf-efficacy played a partial mediating role in the effect of self-disclosure on medical coping strategies for adolescent depression during the COVID-19 pandemic, and the use of a positive self-disclosure mechanism may be anticipated to promote improved self-efficacy and the use of active coping strategies.